2019
DOI: 10.1186/s12889-019-6557-z
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and physical activity patterns related to cardio-metabolic health among Malaysian adolescents: a systematic review

Abstract: Background A sedentary lifestyle and an unhealthy diet are major factors in the increasing prevalence of obesity among Malaysian adolescents. The purpose of this systematic review is to compile the evidence from observational and intervention studies among Malaysian adolescents to evaluate the associations between diet and physical activity (PA) as determinants of cardio-metabolic risk factors. Methods A systematic search of Medline via the PubMed, Science Direct, Cochr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 55 publications
(106 reference statements)
0
30
0
Order By: Relevance
“…Large quantities of fast food consumption and energy dense food is a reason for high-calorie diet in most adolescents (47). A systematic review on Malaysian adolescents revealed that high consumption of energy, macronutrients and skipping meals have an effect on cardio-metabolic health (48). Overall, the interaction of sedentary lifestyle and unhealthy nutrition are deemed to be major influences in the increasing prevalence of risk profiles among the younger generation (49).…”
Section: Discussionmentioning
confidence: 99%
“…Large quantities of fast food consumption and energy dense food is a reason for high-calorie diet in most adolescents (47). A systematic review on Malaysian adolescents revealed that high consumption of energy, macronutrients and skipping meals have an effect on cardio-metabolic health (48). Overall, the interaction of sedentary lifestyle and unhealthy nutrition are deemed to be major influences in the increasing prevalence of risk profiles among the younger generation (49).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that diet-related behaviors can influence individuals' health. For example, dietrelated behaviors are associated with mortality and morbidity of non-communicable diseases [1], risk of certain diseases (cardiovascular disease [9,10], metabolic syndrome [11][12][13], and cancer [9,14]), and all-cause mortality [9]. Knowledge and attitudes indirectly affect individuals' health status by promoting behavior change [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…This strategy may have the potential to offer cost-effective and sustainable support to improve the school canteen food environment. The insights into the effects of price-related approaches to improve food consumption and purchasing behaviours may provide evidence to build appropriate policy and programme responses to the epidemic of obesity and poor diet quality currently facing Malaysian adolescents ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…The intervention was developed based on data obtained from systematic reviews ( 21 , 49 ), reports of the MyHeARTs cohort study ( 48 ), and a related qualitative study ( 50 ). The findings suggested that a school canteen intervention had merit.…”
Section: Methodsmentioning
confidence: 99%